Frequency dependent effects of subthalamic nucleus stimulation in Parkinson's disease. - Fogelson, N; Kühn, A; Silberstein, P; Limousin, P; Hariz, M; Trottenberg, T; Kupsch, A; Brown, P (2005)
Excessive synchronisation of basal ganglia activity at frequencies < 30 Hz is a hallmark of the parkinsonian state, and may contribute to bradykinesia. Accordingly, we electrically stimulated chronically implanted subthalamic macroelectrodes in 10 Parkinson's disease patients, after overnight withdrawal of anti-parkinsonian medication. We compared the effects of stimulation at 0, 5, 10, 15, 20, 25, 30, and ca. 130 Hz by measuring kinesia time (KT) in a tapping task. Although the effects of direct stimulation were small, frequency-response curves demonstrated local peaks at 5-10 Hz and at 20-25 Hz, superimposed upon an overall tendency for KT to reduce with increasing stimulation frequency. This is consistent with the hypothesis that spontaneous activities in these bands might promote bradykinesia.